Impact of Somatosensory Input Deficiency on Subjective Visual Vertical Perception in Children With Reading Disorders - Goulème, Nathalie; Delorme, Richard; Villeneuve, Philippe; Gérard, Christophe-Loïc; Peyre, Hugo; Bucci, Maria Pia (Frontiers in Neurology, 2019)
Purpose: Preliminary evidence indicated that children with reading disorder (RD) may have deviance in their ability to perform high demanding cognitive tasks, such as reading, depending on somatosensory inputs. Till now, only anecdotical reports suggested that improving somatosensory inputs may influence their ability to maintain a stable perception of the visual world despite continuous movements of our eyes, head and body. Here we investigated whether changes in upright perception, the subjective visual vertical, were modulated by somatosensory inputs in a group of children with RD. Method: The subjective visual vertical (SVV) task was used under two distinct conditions, i.e. with or without somatosensory inputs from the foot. We enrolled a group of twenty children with reading disorders and twenty sex-, age-, IQ- matched children with neurotypical development. Results: Responses to SVV task were found to be significantly less accurate in children with RD than in children with neurotypical development (p<0.001). In these latter, SVV response did not depend on somatosensory inputs from the foot. In contrast, children with RD displayed a significant effect of somatosensory inputs on SVV responses under specific tilt conditions (p<0.01). Conclusion: Our results suggested that SVV responses in children with RD could be related to an immaturity for heteromodal sensory integration, including somatosensory inputs.